1986
DOI: 10.1212/wnl.36.2.284
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of twin pairs discordant for Parkinson's disease

Abstract: A previous study of twins with Parkinson's disease (PD) revealed low concordance, suggesting that genetic factors play a minor role in the etiology of PD. To identify possible environmental determinants of PD while maximally controlling for hereditary factors, 31 monozygotic twin pairs discordant for PD were interviewed by telephone. Information about possible risk factors was obtained from systematic and uniform interviews with cases and controls. The only statistically significant result was less cigarette s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 0 publications
2
43
1
Order By: Relevance
“…The aggregated MZ\DZ concordance ratio of 1.2 : 1 found in previous twin studies provided no evidence of a significant genetic risk (Ward et al 1983 ;Barucha et al 1986 ;Marsden, 1987 ;Tanner, 1992 ;Vieregge et al 1992). However, these cross-sectional studies do not allow detection of cases with subclinical disease.…”
Section: Twin Studies and The Role Of Positron Emission Tomographymentioning
confidence: 81%
“…The aggregated MZ\DZ concordance ratio of 1.2 : 1 found in previous twin studies provided no evidence of a significant genetic risk (Ward et al 1983 ;Barucha et al 1986 ;Marsden, 1987 ;Tanner, 1992 ;Vieregge et al 1992). However, these cross-sectional studies do not allow detection of cases with subclinical disease.…”
Section: Twin Studies and The Role Of Positron Emission Tomographymentioning
confidence: 81%
“…A Chinese study reported lower PD risk associated with regular liquor drinking (OR 0.28, 95% CI 0.12-0.65) [146]. In a small co-twin controlled study of 31 monozygotic twin pairs, the unaffected twin drank more alcohol than the affected twin, corresponding to a RR of 0.5 [426].…”
Section: Case-control Studiesmentioning
confidence: 98%
“…Most of these studies included men only. Two small co-twin controlled studies reported a statistically non-significant inverse association between smoking and PD [425,426]. A somewhat larger co-twin controlled study reported that in twin pairs discordant for PD, the unaffected twin smoked more (in pack-years) than the affected twin [427].…”
Section: Smokingmentioning
confidence: 99%
“…However, not all epidemiological studies have been able to demonstrate a statistically significant link between TBI and PD; some studies show a strong correlation (Bower et al, 2003;Goldman et al, 2006;Taylor et al, 1999), while others do not (Bharucha et al, 1986;Rugbjerg et al, 2008;Werneck and Alvarenga, 1999). These observations suggest that the link between TBI and PD may be contingent upon exposure to other risk factors, with TBI being one element sensitizing neurons to other risk factors, as suggested in the ''multiple hits'' hypothesis of PD (Sulzer, 2007).…”
mentioning
confidence: 97%